2003
DOI: 10.4049/jimmunol.170.10.5124
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation and Chromatin Structure Regulate T Cell Perforin Gene Expression

Abstract: Perforin is a cytotoxic effector molecule expressed in NK cells and a subset of T cells. The mechanisms regulating its expression are incompletely understood. We observed that DNA methylation inhibition could increase perforin expression in T cells, so we examined the methylation pattern and chromatin structure of the human perforin promoter and upstream enhancer in primary CD4+ and CD8+ T cells as well as in an NK cell line that expresses perforin, compared with fibroblasts, which do not express perforin. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
117
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 117 publications
(123 citation statements)
references
References 25 publications
5
117
0
Order By: Relevance
“…1a), and regulates the expression of perforin [23]. This enhancer region is CpG‐rich, with 10 identified CpG sites (chr10: 72, 363, 525–72, 363, 863) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1a), and regulates the expression of perforin [23]. This enhancer region is CpG‐rich, with 10 identified CpG sites (chr10: 72, 363, 525–72, 363, 863) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Messenger RNA (mRNA) was isolated from untreated or 2-deoxy-5-azaCtreated T cells, and analyzed using Affymetrix U95A oligonucleotide arrays, as previously described (9).…”
Section: Methodsmentioning
confidence: 99%
“…CD70 transcripts were quantitated by realtime RT-PCR using a LightCycler (Roche, Indianapolis, IN) and previously published protocols (9). The following primers were used: forward, 5Ј-TGCTTTGGTCCCATTGGTCG-3Ј and reverse, 5Ј-TCCTGCTGAGGTCCTGTGTGATTC-3Ј.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased number of cytotoxic CD4 + T cells has been observed in patients with multiple sclerosis, rheumatoid arthritis, inflammatory bowel disease, and acute coronary syndromes [20][21][22][23]. Lu et al (2003) demonstrated that DNA methylation and chromatin structure regulate PRF1 expression in T cells [40]. Moreover, Kaplan et al (2004) showed that DNA methylation inhibitors increased PRF1 expression in CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%